Effectiveness of prehabilitation on outcomes following total knee and hip arthroplasty for osteoarthritis: a systematic review and meta-analysis of randomized controlled trials. - Adebero, Tony; Omana, Humberto; Somerville, Lyndsay; Lanting, Brent; Hunter, Susan W. (Disability & Rehabilitation, 2024)
Purpose: To quantify the effectiveness of prehabilitation prior to total knee and hip arthroplasty (TKA/THA) for osteoarthritis on postoperative outcomes assessed by self-report and performance-based measures. Methods: Embase, MEDLINE, CENTRAL, CINAHL and Scopus (inception-August 2022) were searched for randomized controlled trials. Self-report outcomes were function, health-related quality of life (HRQoL), and pain. Performance-based outcomes were strength, range of motion (ROM), balance, and functional mobility. The RoB 2.0 assessed risk of bias. Random-effects meta-analysis was performed up to 52 weeks after TKA/THA. Results: High risk of bias was found in 24 of 28 trials. Prehabilitation improved function (SMD = 0.50 [95%CI: 0.23, 0.77]), pain (SMD = 0.44 [95%CI: 0.17, 0.71]), HRQoL (SMD = 0.28 [95%CI: 0.12, 0.43]), strength (SMD = 0.72 [95%CI: 0.47, 0.98]), ROM (SMD = 0.31 [95%CI: 0.02, 0.59]), and functional mobility (SMD = 0.39 [95%CI: 0.05, 0.73]) post-TKA. No significant effect of prehabilitation on balance (SMD = 0.28 [95%CI: −0.11, 0.66]) post-TKA. All outcomes assessed had significant heterogeneity (p < 0.01). There were limited and contradictory trials (n = 2) for THA. Conclusion: High risk of bias and significant heterogeneity observed in our meta-analysis prevent conclusions regarding prehabilitation effectiveness on outcomes up to one year after TKA/THA. IMPLICATIONS FOR REHABILITATION: Prehabilitation has been promoted to improve postoperative outcomes and shorten recovery periods after total knee/hip arthroplasty (TKA/THA) for osteoarthritis Prehabilitation improved relevant self-report and performance-based outcomes after TKA surgery A high risk of bias and significant heterogeneity across trials prevent drawing any conclusions More high-quality research is required before recommending the implementation of prehabilitation programs in clinical practice for people awaiting TKA/THA